Applying Concepts of Curriculum Design and Cultural Adaptation: Collaborating on a Dual-Degree Occupational Therapy Program in Mainland China - Julie McLaughlin Gray; Ling Yu (Elena) Meng; Adley Chan; Cameron Chang; Yijun Liu; Liguo Qian; Hui Wang; Ninghua Wang; Yanyan Yang; Mouwang Zhou; Grace T. Baranek (Occupational Therapy International)
Occupational therapy is a profession with origins rooted in Western values. As culture plays an important role in shaping theory and practice, the curriculum design of academic programs that train future rehabilitation professionals should reflect the local context. As part of an international partnership, a dual-degree graduate program in occupational therapy was established between a Chinese and an American university. A team composed of members from both institutions collaborated on culturally adapting an entry-level master’s program in occupational therapy for China, based on a U.S. program, which welcomed its first cohort in September 2019. This article details the timeline and process of program design and adaptation from conception, through implementation to evaluation and revision, with the aim of offering a framework for curriculum adaptation of other academic programs in the U.S. and internationally. The adapted curriculum includes the program mission, vision, and philosophy; the curriculum model with program outcomes and threads; the program scope and sequence; materials and resources; and course-specific objectives, learning activities, and assessments. The authors also share lessons learned through this experience of international collaboration as well as next steps for program evaluation and sustainability. The detailed overview of this international collaboration offers suggestions for individuals and institutions seeking to develop global partnerships and adapt curricula across cultural contexts.